THE CONCEPT OF MORAL STANDARD AND ITS SOCIAL ESSENCE (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the theoretical foundations of the concept of moral norms, its historical formation and modern interpretations from a socio-philosophical perspective. The role of moral norms in the stability of society, the regulation of social relations and the spiritual development of the individual is revealed. Based on the interrelationship with the system of values, tradition and culture, the transformation of moral norms in the context of globalization is highlighted. The importance of moral norms as a mechanism of social control, their relationship with law, religion and spirituality is explained on the basis of a comprehensive approach. The role of moral norms in ensuring the balance between the individual and society is summarized, their practical significance is substantiated by scientific conclusions and promising research directions are identified. The relevance and scientific novelty of this research are indicated.
Keywords: Moral, norm, social, value, society, spirituality, order, control, culture, individual.